Organization and Implementation of a Virtual Summer Study Abroad Program for Japanese Students during the COVID-19 Pandemic - Yoneoka, Judy (Intercultural Communication Studies, 1970)
Organization and Implementation of a Virtual Summer Study Abroad Program for Japanese Students during the COVID-19 Pandemic